Design and engineering of sustainable process systems and supply chains by the P‐graph framework. Issue 2 (27th February 2018) - Cabezas, H.; Argoti, A.; Friedler, F.; Mizsey, P.; Pimentel, J.
Abstract : The design of sustainable manufacturing processes and supply chains is rapidly becoming a critical issue. The reason is the necessity of providing for the needs of a growing human population which is increasingly prosperous across the globe. To this purpose, this review article explores the most important elements of sustainability science and couples them with the P‐graph framework, thereby rendering it possible to design feasible process and supply structures with great ease. Structure is an often‐overlooked aspect of process and supply chain design, in part because even relative simple processes or supply chains can have an enormous number of feasible structures. We further illustrate the application of these ideas with examples of energy generation processes and supply chains. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 624–636, 2018